Prevalence and associated factors of birth injury among neonates admitted at neonatal intensive care unit (NICU) in governmental hospitals of Southwest Ethiopian people regional state, Ethiopia: A multicenteric cross-sectional study - Belay, Alemayehu Sayih; Negese, Ketemaw; Manaye, Gizachew Ayele; Debebe, Shibihon (Frontiers in Pediatrics, 2022)
Abstract Introduction: Neonatal birth injury is the functional or structural damage of the new-born during child birth. Fetal related factors such as macrosomia, fetal weight, and prematurity; maternal related factors such as overly young, poor maternal health, and pelvic anomalies contribute to neonatal birth injury. This study was conducted to assess the prevalence and associated factors of birth injury among neonates admitted to the neonatal intensive care unit in Governmental Hospitals of Southwest Ethiopia. Objective: To assess the prevalence and associated factors of birth injury among neonates admitted to the neonatal intensive care unit in governmental hospitals in Southwest Ethiopia. Method: Hospital-based cross-sectional study design was implemented at Mizan-Tepi University Teaching Hospital, Bonga Gebretsadik Shawo General Hospital, and Tepi General Hospital. A total of 1315 neonates were included in the study using systematic random sampling techniques. Data was entered using Epi-Data version 4.2 and exported to SPSS version 21 for analysis. Logistic regression analysis was conducted to see the association between the dependent and independent variable. Results: The prevalence of neonatal birth injury was 16.7%. Predictors such as primipara, no formal education, mothers with no antenatal care, and mothers whose occupational status were unemployed were 12.27, 2.52, 2.40, and 4.26 times more likely to develop neonatal birth injuries than their counterparts, respectively. Whereas, maternal age within the age range of 25-34 years, and neonates delivered via instrumental delivery were 6.68, and 2.81 times more likely to develop neonatal birth injury compared to those whose age was greater than 34 years and neonates delivered through Cesarean section, respectively. Conclusion: The magnitude of birth injury in the current study was significantly high. Primiparity, mothers with no history of antenatal care follow up, uneducated women, unemployed women, mode of delivery, and maternal age between 25-34 years were strong predictors associated with neonatal birth injury. Therefore, comprehensive maternal health care such as antenatal care follow up and health institution delivery should be promoted and well addressed to all reproductive age women and special attention should be given particularly to pregnant women in order to mitigate problems related to childbirth.